Geochemical Comparison of the Deep Gases From the Sichuan and Tarim Basins, China - Ni, Yunyan; Yao, Limiao; Liao, Fengrong; Chen, Jianping; Yu, Cong; Zhu, Guangyou (Frontiers in Earth Science, 2021)
In order to have a better understanding of the geochemical characteristics of gases from deep depths, gases from the clastic sandstone reservoirs in the Dabei and Keshen gas fields in the Kuqa depression, Tarim basin, and gases from the marine carbonate reservoirs (Ordovician and Cambrian) in the craton area of Tarim basin and Sichuan basin (Yuanba, Longgang, Puguang gas fields) are investigated based on the molecular composition, stable carbon and hydrogen isotopes. Deep gas, either from the clastic sandstone reservoirs or from the marine carbonate reservoirs, is dominated by alkane gas. Gases from Kuqa depression and Sichuan basin are dry gas, with high gas dryness coefficient, 0.976 and 0.999, respectively. Deep gas from the craton area in Tarim basin includes both dry and wet gas. N2 and CO2 are the common nonhydrocarbon components in the deep gas. Deep gas from the continental sandstone reservoirs have no H2S, while gases from the marine carbonate reservoirs often have H2S. The relatively high δ13C2 value in the Kuqa depression indicates the gas was generated from humic type III kerogen, while the relatively low δ13C2 value in the craton area of Tarim basin indicates most of the gas was generated from the marine sapropelic organic matter. Deep gas in Sichuan basin, which has medium δ13C2 value, was generated from both humic type III and sapropelic type II organic matter. Carbon isotopic anomaly such as partial carbon isotopic reversal or relatively heavy carbon isotope is common in the deep gas, which is caused by secondary alteration. Gases from the Dabei gas field have a mean δ2H1 value of –156‰, while gases from the craton area of Tarim basin, and Yuanba and Puguang gas fields in Sichuan basin have relatively heavierδ2H1 value, i.e., average at −130‰ and −122‰, respectively. The abnormally heavier δ2H1 value in Dabei gas field is due to the high thermal maturity and possible saline depositional environment of the source rocks. This study performed a comprehensive comparison of the geochemical characteristics of the deep gases with different origins, which may provide a hint for future exploration of deep gas in the world.